Sistema de control y monitoreo en tiempo real para el análisis del consumo energético en el tablero de distribución principal del bloque B de la Universidad Técnica de Cotopaxi Campus Matriz, periodo 2020. - Muñoz Noroña, Raúl Alejandro (2020)
This technical proposal aimed to implement a control and monitoring system in real-time according to the new era 4.0 industry. It was transcendental to publish the electrical parameters of the main distribution panel of block B at the Universidad Técnica de Cotopaxi, through industrial types of equipment such as Sentron PAC3220, Simatic IoT2040, and HMI linked through the Modbus TCP/IP communication protocol. It also allows us to visualize the variables under study (voltage, current, power, frequency) with the Node-Red platform, which hosts Ubidots in the cloud. The IoT gateway monitored the variables in real-time, allowing communication with the Ethernet network through data storage software. The Sentron PAC3220 energy meter facilitated the measurement of the required electrical quantities; on the other hand, the developed project allowed both students and technical personnel to visualize and control the system locally or remotely quickly. Both manual and automatic design control system of block B charges were carried out by simulation in the Tia-PORTAL and the Node-RED software. It implies to energize and de- energize the main breaker. Also, each sub-panel makes up the lighting and power circuits in the labor schedule to automatically turn on; otherwise, it will remain off.